Continuous nursing for infants with congenital talipes equinovarus undergoing Ponseti therapy and telehealth education for their parents via WeChat: a single center retrospective study - Wang, Xiangxuan; Lin, Kainan; Lin, Jinrun; Xu, Wenchen; Chen, Hui (Frontiers in Public Health, 2024)
Aims This study aimed to evaluate the impact of continuous nursing and telehealth education via WeChat in infants with congenital talipes equinovarus (CTEV) undergoing Ponseti therapy on reducing complications, care burden, and improving the quality of life for parents. Methods This is a single-center retrospective study. From July 2021 to December 2022, 44 CTEV children who undergoing Ponseti treatment in our hospital who received continuous nursing and telehealth education via WeChat (experimental group). In addition, during January 2020 to June 2021, 44 children with CTEV treated with Ponseti in our hospital who received routine nursing and traditional health education were selected as the control group. The incidence of complications, parental care burden and parental quality of life were compared between the two groups. Results There was no significant difference in the demographic characteristics of patients and parents between the two groups, and the groups were comparable (p > 0.05). The incidence of complications including plaster loosens, plaster falling off, pressure ulcer was significantly lower in the intervention group compared to the control group (p < 0.05). Parents in the intervention group experienced significantly lower care burdens compared to those in the control group (p < 0.05). The quality of life of parents in the intervention group was significantly higher than that for the control group (p < 0.05). There were significant differences in the incidence of complications, the care burden of parents and the quality of life of parents between the two groups. Conclusion This study found that continuous nursing and telehealth education via WeChat group during Ponsetis treatment of children with CTEV can effectively reduce complications, reduce the care burden of parents and improve the quality of life of parents. This method is simple and convenient, especially worthy of application and promotion in medically underdeveloped areas.